2016
DOI: 10.1002/pat.3948
|View full text |Cite
|
Sign up to set email alerts
|

Poly(carbonate‐urea‐urethane) networks exhibiting high‐strain shape‐memory effect

Abstract: A challenge in the design of shape‐memory polymers (SMPs) is to achieve high deformability with a simultaneous high shape recovery ratio. Here we explored, whether SMPs featuring large deformation capability and high shape recovery ratios can be created as polymer networks providing two kinds of netpoints based on covalent bonds and physical interactions. As a model system, we selected poly(carbonate‐urea‐urethane)s (PCUUs) synthesized by a precursor route, based on oligo(alkylene carbonate) diols, isophorone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The materials were used without any further purification. The alkylene bis(methylcarbonate)s (BMCs) were synthesized according to previously published procedures [20]. Briefly, in a 2000 cm 3 reactor equipped with a magnetic stirrer, Vigreux column, distillation condenser, and thermometer, 250.0 g (1.43 mol) of 1,10-decanediol and 1000.0 g (11.1 mol) of DMC were placed in the presence of potassium carbonate (3 mol.% referred to 1,10-decanediol), used as a catalyst.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials were used without any further purification. The alkylene bis(methylcarbonate)s (BMCs) were synthesized according to previously published procedures [20]. Briefly, in a 2000 cm 3 reactor equipped with a magnetic stirrer, Vigreux column, distillation condenser, and thermometer, 250.0 g (1.43 mol) of 1,10-decanediol and 1000.0 g (11.1 mol) of DMC were placed in the presence of potassium carbonate (3 mol.% referred to 1,10-decanediol), used as a catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we proposed the method of preparation of SMPs that involved the utilization of OCDs containing long hydrocarbon chains between the carbonate linkages. Obtained poly(carbonate-urea-urethane) networks (PCUUs) exhibited a high-strain shape-memory effect with excellent shape recovery and temporary shape fixation ratios [19,20], as well as a superb reversible bidirectional shape-memory effect [21].…”
Section: Introductionmentioning
confidence: 99%
“…Biobased PLA [ 299 , 300 ]- and vegetable oil [ 297 , 301 , 302 ]-based polyols are pertinent choices to synthesize renewable SMPUs. Moreover, polysaccharides have also been studied as multi-branched polyols [ 303 ], as well as biobased polycarbonate diol [ 304 ] and polyester polyols like PGS diol [ 295 ], PEA and PBA diols [ 305 ]. Important SMPUs properties of the previously mentioned studies and regarding their potential uses in the biomedical area reported in Table 6 .…”
Section: Biobased Pu For Biomedical Applicationsmentioning
confidence: 99%
“…The studies carried out in the CCTP show that highly crystallizable oligo(alkylene carbonate) diols with long hydrocarbon chains between carbonate linkages form temporary netpoints, whereas the permanent shape is defined by the small amount of hydrogen bonds, as well as covalent linkages within their hard segments (allophanate and biuret groups). Two types of isocyanate were used: IPDI [28] and lysine diisocyanate (LDI) [29]. The PCUU networks exhibited 1W-SME with programmed strains up to 1000%, whereby they provided excellent shape fixity (92-97% and 99% in the case of IPDI-and LDI-based PCUUs, respectively) and shape recovery (≥99%) ratios.…”
Section: Poly(carbonate-urea-urethane)s Showing a Shape-memory Effect...mentioning
confidence: 99%